Evil and/or/as the good : omnicentrism, intersubjectivity and value paradox in Tiantai Buddhist thought - Ziporyn, Brook, 1964- (Harvard-Yenching Institute monograph series, 2000)
"Brook Ziporyn provides an overview of the development of Tiantai thought from the fifth through the eleventh centuries in China and contributes to our understanding of Chinese intellectual culture and Chinese Buddhism, as well as to basic ontological, epistemological, and axiological concepts. In the conclusion, he looks at these ideas from a wider perspective by teasing out the philosophical and moral implications of Zhili's ideas."--Jacket